Factors Associated with Outcomes of Acinetobacter baumannii Infection in Ventilator-Associated Pneumonia in the ICU of Dr. Moewardi General Hospital, Surakarta - Putra, Lutfi Lafil Cahya; Saptawati, Leli; Setijanto, Eko; Maryani, Maryani; Maarif, Athok Shofiudin (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: Acinetobacter baumannii is a nosocomial pathogen with high mortality rates in intensive care units (ICUs) and is commonly associated with ventilator-associated pneumonia (VAP). Due to declines in physiological and immune functions, A. baumannii can trigger septic shock complications, thereby increasing mortality risk. This study aimed to identify the risk factors associated with outcomes in VAP patients in the ICU of Dr. Moewardi General Hospital, Surakarta. Methods: This retrospective cohort study was conducted at Dr. Moewardi General Hospital, Surakarta, using patient medical records. Data were analyzed with Chi-square and Mann-Whitney U tests, followed by multiple logistic and linear regression to determine correlations between risk factors and outcomes (recovery, mortality, length of stay/LOS). Results: This study included 80 patients with VAP caused by A. baumannii. Most patients were under 60 years old (52.5%), had good nutritional status (75%), were on ventilators for less than 10 days (63.75%), and had mild comorbidities (51.25%). Moderate-severe comorbidities (p=0.001) and malnutrition (p=0.005) were significantly associated with increased mortality. In addition, ventilator use ≥10 days was significantly associated with LOS (p<0.001). Conclusion: Moderate-severe comorbidities and malnutrition were risk factors for mortality in patients with A. baumannii-related VAP, while ventilator use ≥10 days was a risk factor for prolonged hospitalization. Identifying these factors can help medical personnel manage conditions that worsen VAP outcomes and reduce the risk of A. baumannii-related mortality.